1993
DOI: 10.1002/aja.1001960204
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phospholamban mRNA during early avian muscle morphogenesis is distinct from that of α‐actin

Abstract: We have studied the expression of phospholamban during the early development of chick embryos by in situ hybridization and have compared it to that of a-cardiac and a-skeleta1 actin. In adult cross-striated muscles there is only one phospholamban gene and it is expressed exclusively in the heart and slow muscles. In the heart phospholamban transcripts were first detected at stage 14 in the region of presumptive ventricle and at stage 20 in the atrium. In the myotomal portion of the somites phospholamban mRNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, the whole-mount in situ hybridization showed that phospholamban mRNA signals were stronger in the stage 21 heart (Fig 3B) than in the stage 15 heart (Fig 3A). The overall increase in phospholamban messages between these two hearts has been developing stage hearts was consistent with the previous reports by Toyofuku et al (26) and Toyofuku and Zak (24). When spatial expression patterns of phospholamban were examined in crosssections from the same embryos after whole-mount in situ hybridization, we detected a drastic decrease in the phospholamban expression at the AV canal myocardium and the outflow tract myocardium from stage 15 heart ( Fig 3C) to stage 21 heart (Fig 3D).…”
Section: Phospholamban Is Differentially Expressed In Av Canal Regionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the whole-mount in situ hybridization showed that phospholamban mRNA signals were stronger in the stage 21 heart (Fig 3B) than in the stage 15 heart (Fig 3A). The overall increase in phospholamban messages between these two hearts has been developing stage hearts was consistent with the previous reports by Toyofuku et al (26) and Toyofuku and Zak (24). When spatial expression patterns of phospholamban were examined in crosssections from the same embryos after whole-mount in situ hybridization, we detected a drastic decrease in the phospholamban expression at the AV canal myocardium and the outflow tract myocardium from stage 15 heart ( Fig 3C) to stage 21 heart (Fig 3D).…”
Section: Phospholamban Is Differentially Expressed In Av Canal Regionsupporting
confidence: 92%
“…From the DNA sequence, we found that the clone 15H16 contained 320bp upstream from the poly(A) tail of the chicken phospholamban transcript (24). Phospholamban is a protein regulating the sarcoplasmic reticulum Ca ++ pump activity and thus, plays an important role in the contraction and relaxation of cardiac and slow skeletal muscles (24)(25)(26)(27). Although the expression pattern of phospholamban in developing recently reported in paraffin-sections by in situ hybridization (26,27), its expression in developing AV canal region remained unclear.…”
Section: Phospholamban Is Differentially Expressed In Av Canal Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLN has been found to regulate activity of cardiac SR Ca-ATPase (SERCA2) by the proteinϪprotein interaction ; the de-phosphorylated PLN functions as an inhibitory co-factor of SERCA2 and the phosphorylation of PLN relieves its inhibition for SERCA2 [3,4]. The subsequent activation of SERCA2 leads to enhanced muscle relaxation rates, thereby contributing to the inotropic response to β-adrenergic stimulation.The expression of PLN, detectable in the embryonic heart at an early stage [5,6], is restricted to cardiac, slow-twitch skeletal [7,8] and smooth muscles [9] at adult stage, and its amino acid sequences show a high degree of similarity among many species [8,10,11]. When cardiac muscles are subjected to neurohumoral and hemodynamic stresses, the amounts of PLN mRNA expressed in cardiac SR are greatly altered [12Ϫ14].In previous studies, we have demonstrated that the PLN gene, which is localized in human chromosome 6, and consists of two exons and a 5′ upstream regulatory region [10,11].…”
mentioning
confidence: 99%
“…The expression of PLN, detectable in the embryonic heart at an early stage [5,6], is restricted to cardiac, slow-twitch skeletal [7,8] and smooth muscles [9] at adult stage, and its amino acid sequences show a high degree of similarity among many species [8,10,11]. When cardiac muscles are subjected to neurohumoral and hemodynamic stresses, the amounts of PLN mRNA expressed in cardiac SR are greatly altered [12Ϫ14].…”
mentioning
confidence: 99%